Hubungan Antara Sanitasi Fisik Rumah dan Kebiasaan Merokok dengan Kejadian Penyakit Ispa pada Balita di Wilayah Kerja Puskesmas Sidoarjo - Bambang Trisno (Departement of Mathematics Education, 2024)
This study aims to evaluate the relationship between physical sanitation of the house and smoking habits with the incidence of Acute Respiratory Infections (ARI) in toddlers in the Sidoarjo Health Center Working Area. This research design is an analytic observational study with a cross-sectional approach. The research subjects involved toddlers who live in the Sidoarjo Health Center working area. Data were collected through interviews using a structured questionnaire to parents or caregivers of toddlers, as well as direct observation related to physical sanitation of the house. The results of data analysis will provide a clear picture of the relationship between physical home sanitation and smoking habits with the incidence of ARI in toddlers. This study is expected to contribute to the prevention of ARI in children under five through further understanding of the risk factors that may play a role. The implications of this study can be used as a basis for developing more effective public health programs in the Sidoarjo Health Center Working Area, especially in increasing awareness of home sanitation and reducing smoking habits in the family environment.